Utilization of Youtube Videos during Online Learning to Increase Literacy in English for Middle School Students - Sutanto, Karunia Islami Hartini; Muktiarni, M.; Mupita, Jonah (Bumi Publikasi Nusantara, 2022)
The purpose of this study was to see whether the use of youtube videos could have a good impact on the English literacy of junior high school students. Although several studies research the same thing, the main novelties in this study are that this study has a positive impact on the spirit of teaching English teachers, which is different from the research conducted by Handayani entitled Utilization of youtube During the Covid 19 Pandemic for Learning Media English in Improving Vocabulary and Student Understanding, in this study youtube was only focused on the positive impact felt by students and was not explained about the increase in teacher teaching enthusiasm. This study uses a qualitative descriptive method by observing, interviewing, and explaining facts, and studying the results contained in the research results. The results of this study indicate that the use of youtube during online learning has a positive impact and increases the English literacy skills of junior high school students. In conclusion, students' English literacy skills can be improved by utilizing youtube videos during online learning. The impact that is felt after using youtube during online learning is the increase in students' English literacy and the teachers are more enthusiastic during the online learning period.